The Neonicotinoid Thiacloprid Interferes with the Development, Brain Antioxidants, and Neurochemistry of Chicken Embryos and Alters the Hatchling Behavior: Modulatory Potential of Phytochemicals - Mayada R. Farag; Mahmoud Alagawany; Attia A. A. Moselhy; Enas N. Said; Tamer A. Ismail; Alessandro Di Cerbo; Nicola Pugliese; Mona M. Ahmed (Biology, 2022)
The present experiment was performed to investigate the toxic impact of thiacloprid (TH) on the brain of developing chicken embryos and also to measure its influence on the behavioral responses of hatchlings. The role of chicoric acid (CA) and rosmarinic acid (RA) in modulating the resulted effects was also investigated. The chicken eggs were in ovo inoculated with TH at different doses (0.1, 1, 10, and 100 ug/egg). TH increased the mortality and abnormality rates and altered the neurochemical parameters of exposed embryos dose-dependently. TH also decreased the brain level of monoamines and amino acid neurotransmitters and decreased the activities of acetylcholine esterase (AchE) and Na+/K+-ATPase. The brain activity of catalase (CAT) and superoxide dismutase (SOD) was diminished with downregulation of their mRNA expressions in the brain tissue. When TH was co-administered with CA and RA, the toxic impacts of the insecticide were markedly attenuated, and they showed a complementary effect when used in combination. Taken together, these findings suggested that TH is neurotoxic to chicken embryos and is possibly neurotoxic to embryos of other vertebrates. The findings also demonstrated the antioxidant and neuroprotective effects of CA and RA. Based on the present findings, the CA and RA can be used as invaluable ameliorative of TH-induced toxicity.